DESKRIPSI FAKTOR - FAKTOR KECEMASAN ORANG TUA PADA ANAK PRE OPERASI DI RUANG BEDAH ANAK RSUP DR. M. DJAMIL PADANG - Musymiratul Fauziah; Dwi Novrianda; Hermalinda - (Universitas Andalas, 2017)
Abstract   Anxiety is the emotional response of preoperative most frequently reported in pre operative children, with a prevalence of up to 60% (Akdag et al, 2014). Preoperative anxiety is also felt by the parents of pre operative children. This study aimed to describe the anxiety factors of parent in pre operative children in the pediatric surgery room RSUP Dr. M. Djamil Padang. Type of research was quantitative research with cross sectional study. The sampling technique used accidental sampling with 30 samples. This research held from June 20 to July 30, 2016. Data were analyzed using univariate analysis. Analysis results showed that more than half (53,3%) of respondents were late adulthood, more than half (66,7%) of respondents were mothers, more than half (66,7%) of respondents had a high education, more than half (53,3%) of respondents did not work, more than half (53,3%) of respondents had low knowledge, more than half (56,7%) of respondents had personality type B, more than half (53,3%) of respondents received high support from family members, more than half of respondents received (53,3%) high support form nurses, and average anxiety of respondents was 15,6 and it showed moderate anxiety. Suggested to the nurses in pediatric surgery room to increase the information support like counseling face to face with the parents during the child is in preoperative period, so that can increase the knowledge of parents.   Keywords      :    anxiety, children, parent, pre-operative   Abstrak   Kecemasan merupakan respon emosional peri operatif yang paling sering dilaporkan anak pre operasi, dengan prevalensi hingga 60% (Akdag et al, 2014). Kecemasan pre operasi juga dirasakan orang tua pada anak yang akan dioperasi. Penelitian ini bertujuan untuk mendeskripsikan faktor-faktor kecemasan orang tua pada anak pre operasi di ruang bedah anak RSUP Dr.M.Djamil Padang. Jenis penelitian yang dilakukan adalah penelitian kuantitatif dengan desain deskriptif. Teknik pengambilan sampel menggunakan accidental sampling dengan jumlah sampel 30 orang. Waktu pengumpulan data dilakukan 20 Juni-30 Juli 2016. Analisis data menggunakan persentase. Hasil analisis menunjukkan lebih dari separuh (53,3%) responden berada pada kelompok umur dewasa akhir, lebih dari separuh responden (66,7%) berjenis kelamin perempuan atau Ibu, lebih dari separuh responden (66,7%) memiliki tingkat pendidikan yang tinggi, lebih dari separuh (53,3%) responden tidak bekerja, lebih dari separuh (53,3%) responden memiliki pengetahuan rendah, lebih dari separuh (56,7%) responden memiliki tipe kepribadian B, lebih dari separuh (53,3%) responden menerima dukungan anggota keluarga yang tinggi, lebih dari separuh (53,3%) responden menerima dukungan perawat yang tinggi, dan rata-rata kecemasan adalah 15,67, yaitu kecemasan sedang. Diharapkan kepada perawat ruang bedah anak untuk meningkatkan dukungan informasi berupa konseling face to face kepada orang tua selama anak berada dalam fase pre operasi, sehingga menambah pengetahuan orang tua.   Kata Kunci         :              anak, kecemasan, orang tua, preoperasi